2021
DOI: 10.1021/acs.iecr.1c02914
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Electrically Conductive Membrane-Generated Hydrogen Peroxide and Extreme pH on the Viability of Escherichia coli Biofilms

Abstract: Electrically conductive membranes (ECMs) self-induce antifouling mechanisms at their surface under certain applied electrical currents. Quantifying these mechanisms is critical to enhancing ECMs' self-cleaning performance. Local pH change and H 2 O 2 production are among the most important self-cleaning mechanisms previously hypothesized for ECMs. However, the impacts of these mechanisms have not previously been isolated and comprehensively studied. In this study, we quantified the individual impact of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…This demonstrates that the graphite-PVDF ECM is stable under applied voltage and can be potentially used in water/wastewater treatment applications for, e.g., electrochemical degradation of contaminants. The solution pH was stable during this experiment, which is consistent with results by Halali et al 14 The reason why the pH does not change is the simultaneous production of protons at the anode (2H 2 O → O 2 + 4H + + 4e − ) and hydroxyl ions at the cathode (2H 2 O + 2e − → 2OH − + H 2 ) that neutralize each other in the bulk solution.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This demonstrates that the graphite-PVDF ECM is stable under applied voltage and can be potentially used in water/wastewater treatment applications for, e.g., electrochemical degradation of contaminants. The solution pH was stable during this experiment, which is consistent with results by Halali et al 14 The reason why the pH does not change is the simultaneous production of protons at the anode (2H 2 O → O 2 + 4H + + 4e − ) and hydroxyl ions at the cathode (2H 2 O + 2e − → 2OH − + H 2 ) that neutralize each other in the bulk solution.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…9−12 By applying an electric potential to an ECM, the membrane exerts strong electrostatic repulsion against contaminants. 13,14 Under applied voltages, the membrane can also generate strong oxidizing species (e.g., reactive oxygen and chlorine species) that could inactivate attached microorganisms, 15 reduce/oxidize toxic heavy metal ions (e.g., arsenite-(III) and chromium(VI)), 12,16 and degrade contaminants on membrane surfaces/pores or in water. 17 To fabricate ECMs, the choice of conductive material is a critical consideration.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antifouling mechanisms include electrostatic repulsion of like-charged foulants [11] , electrochemical [12] and electrocatalytic [13] reactions, and gas generation [14] . ECMs have presented several advantages as compared to conventional membranes such as: (a) controllably target foulants at the membrane/water interface which makes them more effective than traditional bulk solution cleaning (biocide dosing, pH adjustment) [15] , [16] , [17] , (b) use electrons, “clean reagents”, as antifouling mediators, making the process less chemical intense and easy to operate, which reduces the handling and storage costs of chemicals [18] , [19] , [20] , and (c) can tailor their antifouling mechanisms by tuning the applied electrical properties (polarity, magnitude, and frequency). Therefore, the antifouling mechanisms can be tailored to exclusively match the application [ 7 , 17 , 21 ].…”
Section: Methods Detailsmentioning
confidence: 99%
“…The inhibition of biofouling from low surface-charged bacteria could be also achieved by H 2 O 2 production through the electroreduction of oxygen. 275,276 The electrochemically produced H 2 O 2 reduced the microbial cell viability and increased cellular permeability, preventing bacterial attachment and ensuring biofilm-free conditions. Additionally, finite element modeling model demonstrated that both electrophoresis and dielectrophoresis are antibiofouling mechanisms for electroconductive membranes.…”
Section: Electrochemical Fouling Mitigation Fouling Monitoring and Re...mentioning
confidence: 99%